A survey of form and compositional practices of Ralph Vaughan Williams, Igor Stravinsky, Paul Hindemith, and Robert Roth in Kyrie of the mass ordinary - Roth, Robert Ray (Kansas State University, 2014)
Ralph Vaughan Williams, Igor Stravinsky, and Paul Hindemith, three prolific composers of the 20th century, wrote for the medium of the mass ordinary in different ways. This report comprises a survey of those composers’ styles using the Kyrie movement of the mass ordinary as the main vehicle of compositional exploration. The results of this compositional survey examine the form and various techniques the composers employ to garner the same emotional response from the listeners of the Kyrie text. The final portion of the report explores the author’s personal compositional contribution to the mass ordinary.
Keywords: Music (0413); Musical Performances (0943)